Ru(II)-catalyzed C-H activation/alkylation of 3-formylbenzofurans with conjugated olefins: product divergence - Srinivas, Kolluru; Siddiqui, Shaziyaparveen K.; Mudaliar, Jyothi K.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2019)
Ru-catalyzed alkylation of 3-formylbenzofuran with acrylates and acrylamides has been described. Branched selectivity with unsubstituted or beta-substituted acrylates/ acrylamides and linear selectivity with alpha-substituted acrylates have been observed. However, in all of the cases, the intermediate alkylation products seem to undergo further reactions, either cycloannulation or deformylation, depending on the substrate employed. For example, with methyl acrylate, the intermediate branched alkylation product underwent cycloannulation with another molecule of methyl acrylate, resulting in a densely functionalized cyclohexene ring formation. On the other hand, in the case of N-monosubstituted acrylamides, the branched alkylation proceeded with intramolecular aldehyde-amide condensation, leading to pyridin-2-one ring annulation. However, with both methacrylate and crotonate, deformylation of the initially formed alkylation products was observed.

Discovery of 3-(benzofuran-2-ylmethyl)-1H-indole derivatives as potential autophagy inducers in cervical cancer cells - Siddiqui, Shaziyaparveen K.; SahayaSheela, Vinodh J.; Kolluru, Srinivas; Pandian, Ganesh N.; Santhoshkumar, Thankayyan R.; Dan, Vipin M.; Ramana, V, Chepuri (Bioorganic & Medicinal Chemistry Letters, 2020)
In this manuscript we have documented the identification of a novel anticancer scaffold 3-(benzofuran-2-yl-methyl)-1H-indole. This scaffold has been designed by tweaking the known bisindolylmethane scaffold of natural products that display a wide range of biological activities. A series of 24 new conjugates have been synthesized and among them 5 derivatives exhibited IC50 values less than 40 mu M against two cervical cancer cell lines SiHa and C33a. Further mechanistic studies of two compounds 3eb and 3ec revealed that the toxicity of these compounds was due to the effective induction of autophagy mediated cell death. The autophagy induction was confirmed by the progressive conversion of LC3I to LC3II and downregulation of p62 in cervical cancer cells.
Keywords: Autophagy; Benzofuran; Bisindolylmethane; Cervical cancer; Friedel-Crafts alkylation